Interview: “I have never Done an Experiment in my Whole Life!” with Mamoun Fansa - Katrin Pres (EXARC Journal)
For almost 25 years, Mamoun Fansa has been one of the defining personalities within the discipline of experimental archaeology. In 1990, he introduced his exhibition `Experimental Archaeology in Germany’. The exposition continued to circulate all over Germany and Europe for the next 14 years. It has helped museums, innovators, and many others, to develop a platform for creative thinking in archaeology.